Pengaruh media video, poster, dan cermin edukasi terhadap peningkatan pengetahuan dan sikap penjamah makanan konsumen: Tinjauan literatur sistematis - Salma Luthfianti; Ratih Kurniasari; Eka Andriani (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background:Food is a basic human necessity for survival. The existence of food handlers provides an important role in maintaining food quality.  Food consumed must meet safety standards so as not to pose a health risk. So knowledge about personal hygiene and food sanitation is needed to be key in preventing the risk of contamination. Food handlers should gain increased knowledge and behavior through education to prevent health risks caused by lack of knowledgeObjectives: This study aims to explore the influence of education related to hygiene and sanitation through the media of videos, posters, and educational mirrors on increasing knowledge and attitudes of food handlers.Methods: This study uses the SLR method of special research design sourced from google scholar and, Pubmed from the last 10 years using inclusion and exclusion criteria in this study following the approach of Population / Problem, Intervention, Comparison Outcome and Study design type (PICOS).Results: The results included three articles that assessed the effects of education using video communication media, posters, and educational mirrors on improving the knowledge and attitudes of food handlers. The installation of personal hygiene posters is effective in all age groups, while visual media such as videos have a significant positive impact with visual media having a positive impact on increasing one's knowledge by 75%-87%.Conclusion: Education through media through the media of videos, posters, and educational mirrors can help increase the knowledge and attitude of food handlers, support safety and hygiene in food provision KeywordsHygiene education, communication media, knowledge and attitudes of food handlers